Tumor-promoting phorbol ester stimulates tyrosine phosphorylation in U-937 monocytes. - Grunberger, G (1984)
Solubilized lectin-purified extracts from human monocyte-like cells (U-937) and freshly isolated human mononuclear cells preincubated in the presence of phorbol 12-myristate 13-acetate (PMA) stimulated phosphorylation of synthetic tyrosine-containing polymers and of casein. Tyrosine phosphorylation was confirmed by phospho amino acid analysis. PMA stimulated phosphorylation of exogenous substrates in a time- and concentration-dependent manner. This phosphorylation reaction did not require addition of phospholipid, diolein, or calcium. Biologically inactive phorbol compounds did not stimulate phosphorylation in this system. In addition, PMA enhanced phosphorylation of a Mr approximately equal to 140,000 protein as well as several other endogenous proteins in the U-937 extracts. PMA treatment stimulated predominantly phosphorylation on tyrosine residues of the Mr 140,000 protein. Tyrosine phosphorylation, typical of growth-promoting peptides such as insulin or epidermal growth factor, is believed to play a role in regulating normal and disordered cellular growth and proliferation. The demonstration of PMA-stimulated tyrosine phosphorylation might provide a clue to the mechanism of cellular differentiation and proliferation induced by the tumor promoter.